Nonlinear consensus for multi-agent systems using positive intractions of doubly stochastic quadratic operators - Abdulghafor, Rawad; Turaev, Sherzod; Mohd Tamrin, Mohd Izzuddin (IIUM Press, 2016)
This technical note addresses a new nonlinear protocol class based on doubly stochastic quadratic operators (DSQO) for a consensus problem in multi-agent systems (MAS). In this technical note, a faster consensus is achieved for MAS by the rules of DSQO with the positive interactions among agents.